PENGARUH PEMBERIAN PUPUK BOKASHI KOTORAN KAMBING TERHADAP KESUBURAN TANAH PADA TANAMAN JAHE MERAH (Zingiber officinable rosc) DI KECAMATAN TINOMBO KABUPATEN PARIGI MAUTONG - Ramlan, Ramlan; Purnaningsih, Putri (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The objective of this research was to investigate the effect of goat manure bokashi on the growth and yields of red ginger plants as well as soil fertility. The study took place between July 2021 and October 2021, conducted in the experimental field at the Faculty of Agriculture, University of Tadulako, using soil samples from Tinombo Sub District, Parigi Moutong District. The application of goat manure resulted in a significant increase in plant height, leaf number, and red ginger tuber weight compared to the control group. Moreover, the overall soil fertility was enhanced by the addition of goat manure bokashi. Notably, the treatment with 30 t/ha of bokashi exhibited the highest soil pH (7.40) with 3.55% organic carbon content, 0.19% total nitrogen, 54.46 mg P2O5/100 g, 69.61 mg K2O /100g, and a cation exchange capacity (CEC) of 22.41 (cmol (+)/kg).